Digital Due Process : Evaluating the Ethical Implications of Cloud-Based eDiscovery Tools in Criminal Investigations - Padmapriya Nagineni, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the growing role of cloud-based eDiscovery in law enforcement and its implications for investigative efficiency and individual privacy rights. As cloud technologies revolutionize legal data processing, enabling real-time analysis of vast data volumes, law enforcement agencies are experiencing unprecedented acceleration in investigations and improvements in legal compliance. However, this technological leap raises significant privacy concerns, particularly regarding access to personal digital footprints such as emails, social media posts, and linked content. The article explores the delicate balance between leveraging cloud-based eDiscovery for enhanced law enforcement capabilities and safeguarding civil liberties in the digital age. Through analysis of case studies, legal frameworks, and emerging ethical guidelines, we evaluate current challenges and propose solutions for responsible implementation of cloud eDiscovery in law enforcement. The article underscores the urgent need for a comprehensive approach that harmonizes technological advancements with robust privacy protections, ensuring that the pursuit of justice does not come at the cost of individual rights in an increasingly digital world.
Keywords: Cloud-Based Ediscovery; Law Enforcement Technology; Digital Privacy Legal Data Processing; Investigative Efficiency